STUDI KOMPARASI LINTAS ZAMAN, PERANAN BADAN PENGAWAS PASAR (AL HISBAH) - Fajar Muhammad, Shofiyul; Muhtadi Ridwan; Khusundin (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The Market Supervisory Authority (al Hisbah) is the agency responsible for monitoring market activities in order to establish fair and fair trade practices in the economic process and ongoing buying and buying interactions. The purpose of this study is to learn about the practice of the Hisbah institutions in the days of the Prophet, Khulafaurr Rasyidin, the Dynasty, the Middle Ages, and the Modern Age. On the occasion of this research, the author uses the library research method (library reaserch), which is a series of approaches based on the collection of materials or methods that come from journals, books, or other sources of writing. In addition to using library studies, the author also uses methods of descriptive analysis. The result of this study explains that the practice of Al-Hisbah in the prophet's time was performed by the Prophet himself as the head of the state and as a muhtasib, but in later times the practice was done by institutions established by the state. In modern times, the practice is no longer carried out by the State but has been grouped according to the fields of supervision carried.